Evaluation of short-interfering RNAs treatment in experimental rabies due to wild-type virus - Appolinario,Camila Michele (2015)
ABSTRACTWe have evaluated the efficacy of short-interfering RNAs targeting the nucleoprotein gene and also the brain immune response in treated and non-treated infected mice. Mice were inoculated with wild-type virus, classified as dog (hv2) or vampire bat (hv3) variants and both groups were treated or leaved as controls. No difference was observed in the lethality rate between treated and non-treated groups, although clinical evaluation of hv2 infected mice showed differences in the severity of clinical disease (p = 0.0006). Evaluation of brain immune response 5 days post-inoculation in treated hv2 group showed no difference among the analyzed genes, whereas after 10 days post-inoculation there was increased expression of 2',5'-oligoadenylate synthetase 1, tumor necrosis factor alpha, interleukin 12, interferon gamma, and C-X-C motif chemokine 10 associated with higher expression of Ngene in the same period (p < 0.0001). In hv2 non-treated group only higher interferon beta expression was found at day 5. The observed differences in results of the immune response genes between treated and non-treated groups is not promising as they had neither impact on mortality nor even a reduction in the expression of N gene in siRNA treated animals. This finding suggests that the use of pre-designed siRNA alone may not be useful in rabies treatment.